THE PROTECTIVE EFFECT OF GREEN TEA EXTRACT ON LEAD INDUCED OXIDATIVE AND DAMAGE ON RAT KIDNEY - N. AIT HAMADOUCHE; A. HADI (International Journal of Pharma and Bio Sciences, 2015)
The role of green tea in protection against nephrotoxicity induced by lead acetate was investigated in rats. Five equal groups, each of ten rats were used. The first group was served as control, the second and third groups were given lead acetate, lead acetate and green tea, respectively, for one month. Pb was given orally at a dose of .4 % w/v, while green tea was given in drinking water at a concentration of (6.6% w/v). Pb administration induced loss of body t and elevation in kidney weight. Significant perturbations of renal function as evidenced via increase in biochemical parameters were observed in treated rats. Renal oxidative damage was observed in Pb-treated rats via augmentation in kidney lipid peroxidation as well as depletion in kidney antioxidant enzymes; catalase, superoxide dismutase and glutathione peroxidase and pathological changes. Co-administration of green tea with lead acetate significantly alleviated these adverse effects. Thus, this study suggests the potent role of green tea in management of injury-induced by lead exposure.